PERAN KATEKIS DALAM KADERISASI PEMIMPIN IBADAT SABDA HARI MINGGU DI STASI SANTA THERESIA TALEKOI PAROKI SANTO PAULUS BUNTOK - Tandroyatno Tandroyatno; Silvester Adinuhgra; Paulina Maria E.W (Sepakat : Jurnal Pastoral Kateketik, 2019)
The purpose of the study was to find out "The Role of Catechists inRegenating Worhisp Leaders for Sunday Service for People at St Theresia Talekoi Parish of Saint Paul Buntok Parish". The method used is a Qualitative Research method with data collection techniques, Observation, and Interview. The data obtained were analyzed using data analysis techniques. The data obtained by the authors from several informants consisting of 9 informants, among others: 4 fathers and 5 mothers from the St Theresia Talekoi station.